2005
DOI: 10.1002/pmic.200401067
|View full text |Cite
|
Sign up to set email alerts
|

Use of two-dimensional gel electrophoresis in predictive toxicology: Identification of potential early protein biomarkers in chemically induced hepatocarcinogenesis

Abstract: Our current approach focused on the identification of potential early protein biomarker signatures which are indicative of the carcinogenic processes in rats exposed to 20 mg/kg of the liver carcinogen N-nitrosomorpholine (NNM). Treated liver was investigated at different timepoints. Therefore, proteins were separated by two-dimensional gel electrophoresis as a first step prior to identification of differentially expressed proteins by mass spectrometry. Proteomic analysis of liver samples after one day of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 31 publications
2
36
0
1
Order By: Relevance
“…[27][28][29] The differentially expressed proteins Rho GDPI 1 and 2, mostly present in the UM primary cell culture, also correlated well with previous reports involving the downregulation of those proteins in late stages of cancer. 30,31 On the other hand, we found proteins previously linked to tumour development or related to cell migration and invasion that were upregulated or exclusively present in the primary cell culture. Interestingly, new proteins were differentially present in the UM cell line like HMG-1, nuclear protein SkiP, and hnRNPA2/B1.…”
Section: Differential Proteome Analysis Of Human Uveal Melanoma Primamentioning
confidence: 78%
“…[27][28][29] The differentially expressed proteins Rho GDPI 1 and 2, mostly present in the UM primary cell culture, also correlated well with previous reports involving the downregulation of those proteins in late stages of cancer. 30,31 On the other hand, we found proteins previously linked to tumour development or related to cell migration and invasion that were upregulated or exclusively present in the primary cell culture. Interestingly, new proteins were differentially present in the UM cell line like HMG-1, nuclear protein SkiP, and hnRNPA2/B1.…”
Section: Differential Proteome Analysis Of Human Uveal Melanoma Primamentioning
confidence: 78%
“…Of the over-expressed proteins, those that may have a role in tumorigenesis or that have been linked to other cancers include: 60 S acidic ribosomal protein P0 overexpression which has been linked to proliferation in breast and liver cancer [27], alpha-actinin 4 which is also differentially expressed in hepatocellular carcinoma [28], annexin V which has been shown to be elevated in chemically induced hepatocarcinoma [29]; as have elongation factor 1 delta [17] and ezrin [19]. Other proteins that have also been shown to be elevated in hepatocellular carcinoma include fibrinogen gamma chain precursor [30], glutathione S transferase [31], glycerol-3-phosphate dehydrogenase [32], histone-binding protein RBBP4 [33] and nucleophosmin [34].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have shown that schistosomiasis alters the expression of enzymes involved in the urea cycle, glycolysis, energy metabolism, and other essential metabolic processes (1,17,41), and the alterations have some similarities with other liver-damaging insults (i.e., liver cancer and hepatotoxicity) (22,66). However, it is clear that some changes may be unique to schistosomiasis.…”
mentioning
confidence: 93%